Perlindungan Hukum Terhadap Korban Tindak Pidana Pencurian Ditinjau Dari Kajian Victimlogi (Studi Putusan No : 20/Pid.B/2017/PN. Mdn) - Jhovindo Sitorus; Rizkan Zulyadi; Wessy Trisna (JUNCTO: Jurnal Ilmiah Hukum, 2020)
Protection against victims of theft is a protection according to Law Number 13 of 2006 concerning Protection of Witnesses and Victims, all efforts are to fulfill rights and provide assistance to provide security to victims that must be carried out by the Witness and Victim Protection Agency (LPSK) or other institutions according to criteria. This protection is given at all stages of the criminal justice process within the judicial environment. The following are the rights of victims and witnesses in Law Number 13 of 2006 concerning Protection of Witnesses and Victims Article 5. The research method in this paper is a normative method that collects library data. The results and discussion of this study is about the protection of victims of theft based on the decision number: 20 / Pid.B / 2017 / PN. Mdn, based on the principle or theory of justice is not fair because there is no restitution or compensation to the victim, and the judge's consideration is to pay attention to things that are lightening and burdensome and pay attention to the absence of justification and forgiveness reasons for imposing a criminal sentence in the form of imprisonment for 2 years against the perpetrators.